Factors Affecting Communication Competency of Farmers in Banka District of Bihar - Mandal, B.K.; De, Dipak (Indian Journal of Extension Education, 2013)
An attempt has been made to study the communication competency of farmers with special reference to dissemination of  paddy cultivation technology. The study was conducted with a sample of 300 farmers drawn randomly from Banka &  Rajaun blocks of Banka district of Bihar. The study revealed that the main factors determining the communication  competency of farmers were presentation skill, sources of information utilization, innovation proneness and annual  income. Among all the nine variables taken for the study, presentation skill emerged as the single most potent factor in  determining the communication competency of farmers.
Keywords: Communication; competence; presentation; skill; technology; dissemination